Geek and Hacker Stories Code, Culture and Storytelling from the Technosphere - Alleyne, Brian; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2019)
Geeks, hackers and gamers share a common 'geek culture', whose members are defined and define themselves mainly in terms of technology and rationality. The members of geek culture produce and circulate stories to express who they are and to explain and justify what they do. Geek storytelling draws on plots and themes from the wider social and cultural context in which geeks live. The author surveys many stories of heated exchanges and techno-tribal conflicts that date back to the earliest days of personal computing, which construct the "self" and the "enemy", and express and debate a range of political positions. Geek and Hacker Stories will be of interest to students of digital social science and media studies. Both geeky and non-technical readers will find something of value in this account.
1. Initialise (key ideas) -- 2. Representing Geeks -- 3. Platform War Stories. 4. Geek Political Narrative -- 5. Notes from a Geek Autobiography. -- 6. Afterword: Coda. .
Keywords: Culture -- Study and teaching; Culture; Mass media; Cultural Studies; Sociology of Culture; Media Sociology